Superhydrophobic and antireflecting behavior of densely packed and size controlled ZnO nanorods - Kumar, Palaniswamy Suresh (2013)
Controlled growth of ZnO nanorods were synthesized using two step low temperature successive ionic layer adsorption and reaction (SILAR), and chemical bath deposition (CBD) approach. By varying the precursor concentrations, the packing density, size, and orientation of ZnO nanorods were tuned successfully. TEM and HRTEM analysis revealed that the deposited ZnO nanorods possessed single-crystal structure with lattice spacing of 0.25 nm. XRD patterns of both ZnO seed layer and nanorod films confirmed a highly crystalline nature with preferential (0 0 2) orientations along the c-axis direction. The surface wettability of ZnO nanorods showed a superhydrophobic behavior with a specific water contact angle (WCA) of ∼160° was achieved without any surface modification or pretreatment. ZnO nanorods also showed a good anti-reflective (AR) property exhibiting a low reflectance of about 6.5%.